2009
DOI: 10.1111/j.1467-9566.2009.01183.x
|View full text |Cite
|
Sign up to set email alerts
|

Managing biomedical uncertainty: the technoscientific illness identity

Abstract: This paper analyses how the biomedical uncertainty of breast cancer contributes to the development of a new type of illness identity that is grounded in biomedical knowledge, advanced technology, and biomedical health and risk surveillance. The technoscientific identity (TSI) develops through the application of sciences and technologies to one's sense of self. Analysing narrative data from 60 in-depth interviews with women diagnosed with breast cancer, this research demonstrates how women diagnosed with breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 46 publications
2
60
0
4
Order By: Relevance
“…'The clinical gaze has been supplemented, if not supplanted, by this molecular gaze, which is itself enmeshed in a ''molecular'' style of thought about life itself' (Rose 2007, p. 12). Clark et al (2003) argue that the rise of the molecular gaze has therefore contributed to the emergence of new subjectivities and identities (see also Sulik 2009).…”
Section: Health Risk and Society 191mentioning
confidence: 98%
See 1 more Smart Citation
“…'The clinical gaze has been supplemented, if not supplanted, by this molecular gaze, which is itself enmeshed in a ''molecular'' style of thought about life itself' (Rose 2007, p. 12). Clark et al (2003) argue that the rise of the molecular gaze has therefore contributed to the emergence of new subjectivities and identities (see also Sulik 2009).…”
Section: Health Risk and Society 191mentioning
confidence: 98%
“…These technologies that diagnose, assess, and produce risk on a molecular and genetic level are increasingly supplanting older imaging technologies (Rose 2001, Robertson 2001, Clark et al 2003. This shift entails a potentially radical reconfiguration of the way that the body and cancer itself are understood (Clark et al 2003, Sulik 2009). We are not intending to suggest that this reconfiguration is necessarily disempowering for cancer survivors.…”
mentioning
confidence: 96%
“…However, the formation of technoscience can also be seen as a socially and culturally significant phenomenon, in that the interrelated co-construction of scientific rationalities and technological devices has an enormous potential to shape and transform social practices, relations, and identities. One important field where this transformative potential of technoscience has been emphasized and vividly debated in recent years is medicine and health care (see for instance Clarke et al 2003, 2009, 2010a; Burri and Dumit 2007; Gibbon and Novas 2008; Kollek and Lemke 2008; Mol 2008; Sulik 2009, 2011; Mathar 2010). In this article, I will therefore concentrate on the field of medicine and explore to what extent and with what consequences we can observe there what some authors have termed a process of “technoscientization” (Clarke et al 2003, 2010b), that is, the transformation of medicine into a field a technoscientific practices.…”
Section: Introductionmentioning
confidence: 99%
“…In short, while we have learned much about how technologies remake human bodies, we need empirical and theoretical works on new biosubjectivities-work that can track formation of technoscientific identities alongside reconfigurations of bodies (Clarke et al 2003(Clarke et al , 2010Sulik 2009 Sulik (2009), for example, found that women with breast cancer diagnoses formed one such identity as a result of their immersion in professional knowledge, placing themselves discursively within this technoscientific framework, receiving support in this identity from the medical system, and prioritizing official classification over their own suffering. Future work might investigate, for example, relations between humans and their brain implants (Morrison 2009), emergent pharmaceutical relations, new "biosocial" collective identities (Gibbon and Novas 2008;Rabinow 1992), and social movements associated with technologies (Kenny 2009).…”
Section: A Special Issue Of Sociology Of Health and Illnessmentioning
confidence: 99%